Henoch-Schönlein Purpura as a Presentation of Chronic Hepatitis B Infection (Journal of Medicine, 2014)
Henoch-Schönlein Purpura (HSP) is characterized by presence of classical triad of palpable purpura, arthritis and abdominal pain 1. HSP may be triggered by bacterial and viral infections, eg. Hepatitis B viral infection. Chronic hepatitis B infection may present with extra hepatic menifestations, vasculitis is an important one and poly arteritis nodosa is more commonly seen. A 30 years old lady presented with abdominal pain, palpable rashes over trunk, lower limb, which were consistent with HSP along with joint pain more on knees and ankles. She was diagnosed as a case of chronic hepatitis. HSP is not very uncommon among patients attending hospitals of Bangladesh, but its relation with Hepatitis B virus (HBV) or any other infective agent is not always searched. In our case HSP presented as an extra hepatic manifestation of chronic hepatitis B infection. The extra hepatic manifestations of chronic hepatitis B are associated with deposition of circulating HBV Ag-Ab immune complexes.DOI: http://dx.doi.org/10.3329/jom.v14i2.19692 J Medicine 2013, 14(2): 210-212